The Fourier Decomposition for a Radiative-Transfer Problem with an Asymmetrically Reflecting Ground - L. B. Barichello, R. D. M. Garcia; C. E. Siewert (Journal of Quantitative Spectroscopy and Radiative Transfer, 1996)
n/a
n/a